Single Locoregional Triamcinolone Injection Immediately After Esophageal Endoscopic Submucosal Dissection Prevents Stricture Formation. Issue 2 (February 2017) - Nagami, Yasuaki; Shiba, Masatsugu; Ominami, Masaki; Sakai, Taishi; Minamino, Hiroaki; Fukunaga, Shusei; Sugimori, Satoshi; Tanaka, Fumio; Kamata, Noriko; Tanigawa, Tetsuya; Yamagami, Hirokazu; Watanabe, Toshio; et al.
Abstract : OBJECTIVES: : Although endoscopic submucosal dissection (ESD) is an efficient treatment for superficial esophageal cancer, it is associated with stricture formation after wide‐circumference resection that leads to a low quality of life. Although locoregional steroid injections prevent stricture formation, a randomized comparative study did not report any advantages associated with steroid injection. We evaluated the prophylactic efficacy of a single locoregional triamcinolone injection for stricture formation after esophageal ESD. METHODS: : This was a retrospective matched case‐control study using propensity score matching (PSM). Between April 2006 and July 2015, a total of 602 patients with superficial esophageal neoplasia underwent ESD. Among them, 189 patients with mucosal defects that spanned more than 2/3 of the esophageal circumference were included. After exclusion, 150 patients were enrolled. Triamcinolone acetonide (80 mg) was injected into the residual submucosal layer of the resected region immediately after ESD. PSM was performed to reduce the effects of selection bias for steroid injection. The primary outcome was the incidence of stricture formation. The secondary outcome was the number of balloon dilatation procedures required to resolve the stricture formation. RESULTS: : Thirty‐seven patients, with and without triamcinolone injection each, were matched after PSM. The incidence of stricture formation decreased from 45.9% (17/37) without triamcinolone injection to 18.9% (7/37) with triamcinolone injection ( p =0.016). After matching, the mean number of balloon dilatation procedures required also decreased from 2.8±4.6 to 0.6±1.5 times ( P <0.01). CONCLUSIONS: : A single locoregional triamcinolone injection efficiently prevented stricture formation after esophageal ESD.